Complexes of terrestrial molluscs of various biotopes in the Gissar Range, Uzbekistan - Jasur Kudratov; Abduvaeit Pazilov; Dilnoza Zokirova; Bekzod Otakulov; Jamshed Jalilov; Xulkar Urinova; Fazlitdin Khalimov; Zuvaidullo Izzatullaev (Acta Biologica Sibirica, 2024)
The article presents the results of studying the complexes of terrestrial molluscs of various biotopes in the Gissar Range, Uzbekistan. Taxonomic identification of terrestrial molluscs collected from 13 biotopes in 4 altitude regions, determination of individual species’ density, and assessment of the similarity of species content among biotopes was carried out. Forty-six species of molluscs are found in the studied biotopes. Biotopes no. 5 (along ditches among thickets of grass, under stones), no. 10 (near springs among grasses), and no. 11 (on the banks of small streams among thickets of grasses) were found to maintain the highest species richness. The most common species in the studied biotopes are Cochlicopa lubrica, Vallonia costata, and Pupilla muscorum.